Covid-19 among College Students in Pekanbaru: How Much Do They Know? - Yumarlin, Kiki; Fitri, Lidia; Ritawani, Evis; Rustam, Musfardi (Diversity: Disease Preventive of Research Integrity, 2022)
Coronavirus Disease 2019 or called Covid-19 which is the cause of a public health emergency, is a new type of virus that has never been previously identified in humans and has no known transmitter. The Covid-19 pandemic is a health problem due to high morbidity and mortality cases. The purpose of the study was to describe student knowledge about Covid-19 at the Helvetia Midwifery Academy Pekanbaru. This type of research was a quantitative analytic descriptive design. The population in this study was 122 female students with a total sampling technique. Data were collected using a questionnaire sheet and analyzed univariately. The results showed that the majority of Helvetia Midwifery Academy students' knowledge about Covid-19 was 66.4% less. This study found that there were still many female students who had less knowledge about Covid-19, especially in terms of maintaining distance. Respondents are expected to increase their knowledge by reading, finding out, and following the development of information related to Covid-19 on trusted social media in order to break the chain of transmission of Covid-19.